The Effectiveness Group Counseling with Role Playing to Improve Self-Control - Irhamna, Nuning; Sugiyo, Sugiyo; Awalya, Awalya (Jurnal Bimbingan Konseling, 2022)
Self-control is significant for individuals to control inappropriate social and helps them to adapt to an environment. This study aimed to determine the effectiveness of group counseling with role playing technique model to improve students’ self-control. It used an experimental method with pre-experimental (one group pretest-posttest design) and involved 6 students with low self-control. In collecting students’ data, this study used Self-Control Scale (SCS) whose alpha coefficient of 0.85. Based on wilcoxon statistical test, the intervention given was able to improve students’ self-control (Z=-2.20, p < 0.05). In conclusion, the group counseling with role playing technique can be an alternative for maximizing a group guidance service quality. Further study implications and limitations are discussed in the discussion chapter.